Photochemical Reaction of 7,12-Dimethylbenz[a]anthracene (DMBA) and Formation of DNA Covalent Adducts - Yu, Hongtao (Molecular Diversity Preservation International (MDPI), 2005)
DMBA, 7,12-dimethylbenz[a]anthracene, is a widely studied polycyclic aromatic hydrocarbon that has long been recognized as a probable human carcinogen. It has been found that DMBA is phototoxic in bacteria as well as in animal or human cells and photomutagenic in Salmonella typhimurium strain TA102. This article tempts to explain the photochemistry and photomutagenicity mechanism. Light irradiation converts DMBA into several photoproducts including benz[a]anthracene-7,12-dione, 7-hydroxy-12-keto-7-methylbenz[a]anthracene, 7,12-epidioxy-7,12-dihydro-DMBA, 7-hydroxymethyl-12-methylbenz[a]anthracene and 12-hydroxymethyl-7-methylbenz[a]anthracene. Structures of these photoproducts have been identified by either comparison with authentic samples or by NMR/MS. At least four other photoproducts need to be assigned. Photo-irradiation of DMBA in the presence of calf thymus DNA was similarly conducted and light-induced DMBA-DNA adducts were analyzed by (32)P-postlabeling/TLC, which indicates that multiple DNA adducts were formed. This indicates that formation of DNA adducts might be the source of photomutagenicity of DMBA. Metabolites obtained from the metabolism of DMBA by rat liver microsomes were reacted with calf thymus DNA and the resulting DNA adducts were analyzed by (32)P-postlabeling/TLC under identical conditions. Comparison of the DNA adduct profiles indicates that the DNA adducts formed from photo-irradiation are different from the DNA adducts formed due to the reaction of DMBA metabolites with DNA. These results suggest that photo-irradiation of DMBA can lead to genotoxicity through activation pathways different from those by microsomal metabolism of DMBA.